Giat Nguopin Wanita Bali di Desa Tegal Tugu Gianyar - Lini, Eka Setya; Nerawati, Ni Gusti Ayu Agung; Arini, Ni Wayan (Metta : Jurnal Ilmu Multidisiplin, 2023)
Ceremonial activities in Bali cannot be separated from one of the implementations of the three basic frameworks carried out by Hindus. This relates to preparing ceremonies or proper facilities that cannot be carried out alone but requires assistance or assistance from other people, neighbors, or krama banjar. This tradition of mutual assistance, often called nguopin, has been passed down from generation to generation and is still maintained today. This research aims to describe the Balinese women's nguopin activities in Tegal Tugu Village, Gianyar. The method used is a qualitative method. The data used are primary data and secondary data. Preliminary data were obtained through interviews with informants about the Balinese women's nguopin activity in Tegal Tugu Village, Gianyar. Secondary data is related to the documentation of the active nguopin implementation. The research results state that; 1) the functional performance of nguopin has been around for a long time and is still being preserved in the five yadnya activities, such as sanggah or merajan piodalan ceremonies, pawiwahan, cremation, mecaru, and others. 2) The active role of Balinese women is to create a sense of belonging, togetherness, mutual assistance among Balinese women or karma. 3) In the view of Hindus, nguopin is contained in the Bhagavad Gita; 4) The educational value of nguopin is the value of ethics education, harmony education, and value social education.